Application of Problem Based Learning Model on Pythagorean Theorem Material to Improve Student Learning Outcomes for Class VIII SMP Negeri 2 Mandrehe - Asrar Aspia Manurung; Famati Fama Gulo (UMSU, 2021)
This research began with the problem of the low Mathematics learning outcomes of class VIII students of SMP Negeri 2 Mandrehe, West Nias Regency on the Pythagorean Theorem material, under the Minimum Completeness Criteria (KKM) of 67. Of the 27 total students, only 12 students reached the KKM, which is around 44%. . The purpose of this study was to improve the learning outcomes of eighth grade students of SMP Negeri 2 Mandrehe. This research is a classroom action research (CAR) which is carried out in two cycles. This research was conducted in class VIII of SMP Negeri 2 Mandrehe in the 2019/2020 school year. Based on the results of the discussion and analysis, it is concluded that the application of the problem based learning (PBL) model can improve student learning outcomes on the Pythagorean theorem material. The increase in teacher activity in the learning process is caused by the teacher using a problem based learning (PBL) learning model. Student learning outcomes have increased from cycle I to cycle II. Student learning outcomes before the action reached the KKM only 12 students with a classical average of 44%. Then in the first cycle, only 18 students reached the KKM with a classical average of 67%. Cycle II students who reach the KKM 25 students with a classical average of 93%